Development and Validation of Assay Method for the Estimation of Moxifloxacin in Bulk and Pharmaceutical Formulations by RP-HPLC - Siraj, Zahid; Adil, Omair; Amin, Bakht; Tahiri, Iftikhar Ahmed (Indian Journal of Pharmacy Practice)
Background: A simple, specific and isocratic reversed phase-high performance liquid chromatography (RP-HPLC) method with UV detection at 293 nm and column Agela Technology, C18, (Venosil XBP, 4.6 mm×250 mm, 10 μm) was developed and validated for analysis of Moxifloxacin hydrochloride (MOXI) in presence of its degradation products. The method was validated in accordance with International Conference on Harmonization (ICH) guidelines. Materials and Methods: The study used a mobile phase consisting of a phosphate buffer and methanol (18:7 v/v), with a flow rate of 1.3 mL/min. The temperature was maintained at 50ºC using a column oven. Additionally, 0.1N HCl was used as the diluent. Results: The retention time of the MOXI was found at 9.99 min. The calibration curves were linear with correlation coefficient (R2) of 0.999. The detection and quantification limit were found as 0.029 μg mL-1 and 0.095 μg mL-1 respectively. Conclusion: The proposed method was found to be sensitive, specific and was successfully applied for the estimation of MOXI in pharmaceutical formulations. Innumerable analytical measurements are conducted for the estimation of MOXI in pharmaceutical formulations, so the proposed analytical method leads to provision of cost effective by using low-cost diluents and reagents.
Keywords: Moxifloxacin; High pressure liquid chromatography; International conference on harmonization; validation; HPLC; ICH